ELearning significantly improves maternity professionals' knowledge of the congenital cytomegalovirus prevention guidelines. (29th March 2022) - Smithers‐Sheedy, Hayley; Swinburn, Katherine; Waight, Emma; King, Ruth; Hui, Lisa; Jones, Cheryl A.; Daly, Kate; Rawlinson, William; Mcintyre, Sarah; Webb, Annabel; Badawi, Nadia; Bowen, Asha; et al.
Abstract : Aims: Cytomegalovirus (CMV) is a preventable cause of neurodevelopmental disability. Australian guidelines recommend that pregnant women are informed about CMV to reduce their risk of infection; however, less than 10% of maternity health professionals routinely provide prevention advice. The aim was to develop and evaluate the effectiveness of an eLearning course for midwives to improve knowledge and confidence about CMV. Materials and Methods: Participants undertaking the course between March and November 2020 were invited to complete an evaluation questionnaire: before the course (T1), immediately after (T2) and three months post completion (T3). A linear mixed model was used to evaluate change in participant scores; P < 0.05 was considered statistically significant. Results: Midwives (316/363, 87%), midwifery students (29/363, 8%) and nurses (18/363, 5%) participated. At T1 80% indicated they had not received education about CMV. Total adjusted mean scores for questionnaires completed between T1 ( n = 363) and T2 ( n = 238) increased significantly (from 17.2 to 22.8, P < 0.001). Limited available T3 scores ( n = 27) (−1.7, P < 0.001), while lower than T2, remained higher than at T1 (+3.6, P < 0.001). Participants' awareness of CMV information resources improved from 10 to 97% from T1 to T2. Confidence in providing CMV advice increased from 6 to 95% between T1 and T2 ( P < 0.001) and was maintained at T3. Almost all (99%) participants indicated they would recommend the course to colleagues. Conclusion: Participants who completed the eLearning course had significantly improved knowledge and confidence in providing advice about CMV. Programs targeting other maternity health professionals should be considered, to further support the implementation of the congenital CMV prevention guidelines.